Sonographic assessment of low muscle quantity identifies mortality risk during COVID‐19: a prospective single‐centre study. Issue 1 (8th December 2021) - Kremer, Wolfgang M.; Labenz, Christian; Kuchen, Robert; Sagoschen, Ingo; Bodenstein, Marc; Schreiner, Oliver; Wörns, Marcus A.; Sivanathan, Visvakanth; Weinmann, Arndt; Galle, Peter R.; Sprinzl, Martin F.
Abstract: Background: Assessment of muscle quantity by sonographic muscle indices could help identify patients at risk for fatal outcome during coronavirus disease‐2019 (COVID‐19). The aim of this study was to explore sonographic muscle indices as predictors of COVID‐19 outcome and to test the feasibility of sonographic muscle measurement in an isolation context. Methods: Muscle indices, derived from the psoas muscle or thigh muscles, were quantified by sonography in a cohort of patients without COVID‐19 to obtain reference values for low muscle quantity. Gender‐specific median of different muscle indices were defined as threshold value for low muscle quantity. The prognostic relevance of low muscle quantity, was prospectively explored in two cohorts of hospitalized COVID‐19 patients. Optimal muscle index cutoff values predictive for 30 day mortality during COVID‐19 were determined by receiver operating characteristic‐area under the curve and Youden index calculation. Muscle quantity and known prognostic factors of COVID‐19 were analysed by multivariable log‐regression. Results: Compared with other muscle indices, the psoas muscle area index (PMAI) showed the most favourable characteristics to predict outcome of COVID‐19 disease. Sonographic morphometry of patients without COVID‐19 ( n  = 136) revealed a gender‐specific median for PMAI (male: 291.1 mm 2 /m 2, female 260.6 mm 2 /m 2 ) as threshold value of low muscle quantity. Subsequently, COVID‐19 patients (Cohort I: n  = 58; Cohort II: n  = 55) were prospectively assessed by bedside sonography. The studied COVID‐19 patients developed a critical course of disease in 22.4% (Cohort I: n  = 13/58) and 34.5% (Cohort II: n  = 20/55). Mortality rate reached 12.1% (Cohort I: n  = 7/58) and 20.0% (Cohort I: n  = 11/55) within 30 days of follow up. COVID‐19 patients with a PMAI below the gender‐specific median showed a higher 30 day mortality in both COVID‐19 cohorts (log rank, P  < 0.05). The optimal PMAI cutoff value (206 mm 2 /m 2 ) predicted 30 day mortality of hospitalized COVID‐19 patients with a sensitivity of 72% and specificity of 78.5% (receiver operating characteristic‐area under the curve: 0.793, 95% confidence interval 0.671–0.914, P  = 0.008). Multivariable log‐regression analysis of PMAI, age, gender, BMI and comorbidities confirmed an independent association of low PMAI with 30 day mortality of COVID‐19 patients ( P  = 0.018). Conclusions: Sonographic morphometry provides reliable muscle quantification under hygienic precautions and allows risk stratification of patients with COVID‐19.